3-D object recognition using a new invariant relationship by single-view - Roh, Kyoung Sig; Kweon, In So (Pattern recognition, 2000)
We propose a new method for recognizing three-dimensional objects using a three-dimensional invariant relationship and geometric hashing by single-view. We develop a special structure consisting of four co-planar points and any two non-planar points with respect to the plane. We derive an invariant relationship for the structure, which is represented by a plane equation. For the recognition of three-dimensional objects using the geometric hashing, a set of points on the plane, thereby satisfying the invariant relationship, are mapped into a set of points intersecting the plane and the unit sphere. Since the structure is much more general than the previous structures proposed by Rothwell et al. (Oxford University TR-OUEL 1927/92, 1992) and Zhu et al. (Proceedings of the 12th International Conference on Robotics and Automation, Nagoya, Japan, 1995, pp. 1726–1731), it gives enough many voting to generate hypotheses. We also show that from the proposed invariant relationship, an invariant for the structure by two-view and an invariant for a structure proposed by Zhu et al. (Proceedings of the 12th International Conference on Robotics and Automation, Nagoya, Japan, 1995, pp. 1726–1731) can also be derived. Experiments using three-dimensional polyhedral objects are carried out to demonstrate the feasibility of our method for three-dimensional objects.